2022
DOI: 10.24953/turkjped.2021.4855
|View full text |Cite
|
Sign up to set email alerts
|

A novel Mecom gene mutation associated with amegakaryocytic thrombocytopenia in a premature infant

Abstract: Background. Hereditary bone marrow failure syndromes are a category of biologically different syndromes that can cause cytopenia in at least one hematopoietic cell lineage. Case. We present a 29-week-old male infant who had a low Apgar Score, advanced delivery room resuscitation, widespread petechial rash, and ecchymoses at birth, without any dysmorphic features. Initial laboratory tests revealed bicytopenia (platelet count 7x10 3 /uL, hemoglobin of 3.9 g/dL, neutrophil 2.0x103 /uL) with findings of disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recent studies have identified MECOM variants in individuals with congenital bone marrow failure with or without RUS ( supplemental Figure 1 ). 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 19 , 20 , 21 , 22 In addition, other skeletal anomalies of the forearms and hands, congenital heart diseases, and renal anomalies were also involved with variable penetrance. 1 , 2 , 4 , 5 , 6 , 7 , 9 , 20 , 22 The term “MECOM-associated syndrome” is proposed to represent this heterogeneous disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have identified MECOM variants in individuals with congenital bone marrow failure with or without RUS ( supplemental Figure 1 ). 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 19 , 20 , 21 , 22 In addition, other skeletal anomalies of the forearms and hands, congenital heart diseases, and renal anomalies were also involved with variable penetrance. 1 , 2 , 4 , 5 , 6 , 7 , 9 , 20 , 22 The term “MECOM-associated syndrome” is proposed to represent this heterogeneous disease.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 19 , 20 , 21 , 22 In addition, other skeletal anomalies of the forearms and hands, congenital heart diseases, and renal anomalies were also involved with variable penetrance. 1 , 2 , 4 , 5 , 6 , 7 , 9 , 20 , 22 The term “MECOM-associated syndrome” is proposed to represent this heterogeneous disease. 2 Individuals with congenital bone marrow failure without RUS exhibit nonsense, insertion/deletion, or splicing variants that result in a premature termination codon in MECOM ( supplemental Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation